Contemporary management of pancreas cancer in older people. (March 2021) - Baltatzis, Minas; Rodriquenz, Maria Grazia; Siriwardena, Ajith K.; De Liguori Carino, Nicola
Abstract: As the population of western countries is aging, the number of patients diagnosed with cancer is growing. Therefore older people, more susceptible to develop pancreatic malignancy, will likely represent the prototype of a pancreatic cancer patient in the near future. Diagnostic modalities utilised for younger patients are also applicable for older individuals. There is accumulative evidence that biological age is not an independent factor predicting poor outcome in elderly patients with resectable disease undergoing surgery, however increased postoperative morbidity and mortality within the elderly group has also been reported. Adjuvant chemotherapy should be offered in all patients with good performance status regardless of their age. Palliative measures for unresectable tumours including relief from biliary and duodenal obstruction as well as chemotherapy should be considered in non-frail patients with reasonable life expectancy. Palliative chemotherapy options are FOLFIRINOX or gemcitabine/nab-paclitaxel for patients with good performance status (0–1) and gemcitabine alone for patients with performance status 2–3. The cornerstone for improving the outcomes of the elderly age group is careful patient selection and perioperative optimization of those who have indication for surgery. Patients and their carers should be involved in the decision making process with emphasis on the expected functional recovery after the proposed treatment modality. The presence of geriatricians in the multidisciplinary team meetings is crucial in order to identify the optimal treatment pathway for elderly patients. Geriatric input regarding peri-habilitation pathways to improve surgical outcomes, to decrease mortality and to expedite patients' functional recovery is highly recommended. Highlights: Diagnostic modalities should be the same for elderly patients as in younger population. Age is not an independent contraindication for surgery. Geriatric specialists have a crucial role in designing the appropriate management and in optimising the patients for surgery, chemotherapy or both. FOLFIRINOX, gemcitabine and nab-paclitaxel are well tolerated by the elderly population. Holistic care is recommended to facilitate elderly patients' functional recovery after treatment.